2016
DOI: 10.4103/2249-4863.197267
|View full text |Cite
|
Sign up to set email alerts
|

Status of governmental oral health care delivery system in Haryana, India

Abstract: Background:Health system should be organized to meet the needs of entire population of the nation. This means that the state has the direct responsibility for the health of its population and improving the quality of life through research, education, and provision of health services. The present study was conducted to evaluate the government oral health care delivery system in Haryana, India.Materials and Methods:The present cross-sectional study was conducted among 135 dental care units (DCUs) of various prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Among the 18 PHCs, most of the dental units present at the PHCs [16 (89%)] were established and managed by the private dental colleges/hospital with a MoU and the remaining 2 (10.50%) were managed by government dental college and state government, whereas in the study done by Vashist et al ., all the dentists were recruited by state government which shows a need for Karnataka state government to recruit dental officers at all PHCs to achieve optimal oral health-care delivery. [6]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 18 PHCs, most of the dental units present at the PHCs [16 (89%)] were established and managed by the private dental colleges/hospital with a MoU and the remaining 2 (10.50%) were managed by government dental college and state government, whereas in the study done by Vashist et al ., all the dentists were recruited by state government which shows a need for Karnataka state government to recruit dental officers at all PHCs to achieve optimal oral health-care delivery. [6]…”
Section: Discussionmentioning
confidence: 99%
“…Adequate infrastructure, which includes buildings, equipment, supplies, and communication equipment, forms a crucial part of the health services. [6]…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that dental care units having no ultrasonic scaler relied on option of hand scaling which indeed is a tiring and time consuming procedure, thus affecting the efficiency of dental manpower. 13…”
Section: Discussionmentioning
confidence: 99%